2019
DOI: 10.5185/amlett.2019.2230
|View full text |Cite
|
Sign up to set email alerts
|

Facile synthesis of novel tough and highly flexible biodegradable membranes for water microfiltration

Abstract: Microporous polymeric membranes have found great applications in the area of water desalination and wastewater treatment, tissue engineering, drug delivery, and bone regeneration. The ability to create micro-size pores within a polymeric membrane allows for cavity formation that could form channels through which substances may permeate or percolate easily. The majority of these applications though, require micro-size porous membranes with small pore size and narrow pore-size distribution as to allow the contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…According to previous reports, 28 the existence of hydrogen bonding between the –OH of CA and the –C O of PLA was attributed to limited extensibility of PLA chains. It was believed here that the increase of magnitude of modulus could be the consequence that the presence of 30% CA restrained the mobility of PLA chains via interface interaction of hydrogen bonds.…”
Section: Resultsmentioning
confidence: 64%
See 3 more Smart Citations
“…According to previous reports, 28 the existence of hydrogen bonding between the –OH of CA and the –C O of PLA was attributed to limited extensibility of PLA chains. It was believed here that the increase of magnitude of modulus could be the consequence that the presence of 30% CA restrained the mobility of PLA chains via interface interaction of hydrogen bonds.…”
Section: Resultsmentioning
confidence: 64%
“…It was related to the repulsive forces between the two slightly hydrophobic polymers that further led to the decline of the G ′ and G ′′ of the polymeric blend. 28 Therefore, the excessive addition of CA had a negative effect on the printability of the ink. Hence, the results clearly demonstrated that the ink of PLA/CA at 70 : 30 weight ratio was the most desirable material for extrusion.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The nanoporous membranes were prepared using the solvent casting technique with a mixture of PLA and PU as described in [15], with 10% cellulose acetate (CA) and 50% NaCl crystals (pore formers). They were then soaked in 0.1 M of the metal salt solution for three days on an orbital shaker, then added to a 0.5 M NaBH4 aqueous solution and was shaken for 24 h on an orbital shaker at room temperature to allow all the metal salt ions to be reduced to metal nanoparticles.…”
Section: In Situ Preparation Of Metal Loaded Porous Membranesmentioning
confidence: 99%